2016
DOI: 10.1186/s13104-015-1799-z
|View full text |Cite
|
Sign up to set email alerts
|

Solitary langerhans cell histiocytosis in an adult: case report and literature review

Abstract: BackgroundLangerhans cell histiocytosis (LCH) is a disease that often affects children, but can also occur in adults and smokers. Oral manifestations are unusual and are characterized by bone pain, tooth mobility, necrotic ulcers and local edema. The aim of this paper is to describe a clinical case of LCH in an oral cavity that mimicked oral squamous cell carcinoma.Case presentationA male, 63 years old, complaining about a “wound in the mouth” for 6 months, without any pain or spontaneous bleeding. His medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…In the case of LCH, systemic treatment is crucial for the arrest of periodontal disease. In agreement with previous reports and reviews of the literature, 4‐15 the present case suggests that periodontal lesions can be diagnostic criteria for LCH. The present report also demonstrates the need for a concise and strict multidisciplinary approach for these patients, even when they are not compliant with therapy.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the case of LCH, systemic treatment is crucial for the arrest of periodontal disease. In agreement with previous reports and reviews of the literature, 4‐15 the present case suggests that periodontal lesions can be diagnostic criteria for LCH. The present report also demonstrates the need for a concise and strict multidisciplinary approach for these patients, even when they are not compliant with therapy.…”
Section: Discussionsupporting
confidence: 93%
“…The clinical presentation is heterogeneous, and the patient may be asymptomatic, especially in cases of solitary, osteolytic lesions, or have severe symptoms, in the systemic form of the disease. In both cases, LCH lesions may be present in any tissue or organ, involving the oral cavity and periodontal tissues 3‐15 . Diagnosis of LCH requires a tissue biopsy and the demonstration of CD1α antigenic determinants on the surface of lesional cells 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment modalities may range from (1) surgical procedures, like curettage or excision, (2) irradiation, (3) intralesional steroid injection and (4) chemotherapy. The choice of treatment should be based on the pattern of involvement, that is, single or multisystem involvement and also the size, site of the lesion and age of the patient 16. Curettage is best for easily assessable unifocal small size lesions,17 as was done in our case.…”
Section: Discussionmentioning
confidence: 89%
“…A key feature of this neoplasm is its clonal derivation from a single cell, which does not necessarily mean malignancy [ 6 ]. On the other hand, it is reported that proinflammatory cytokines and chemokines as well as oncogenic B-type Raf kinase (BRAF) gene mutations are involved in the pathogenesis of EG [ 10 ]. BRAF mutations are present in several malignant neoplasias including papillary thyrd carcinoma [ 11 ].…”
Section: Discussionmentioning
confidence: 99%